Concept of matrix readiness methodology application development for managing innovative digitalization projects - V. A. Shiboldenkov; D. A. Bastamova; K. A. Yakovleva (Вестник университета)
The article is devoted to the development of using matrix readiness concept to manage innovative digitalization projects. One of the concept features is the application of existing methodologies for assessing the readiness level of innovation and considering them in the conditions of the VUCA-world and the BANI-world. To do this, these concepts, their structure, influence and role in the modern world have been described in more detail. To develop the concept, existing methodologies were used to assess the technology readiness level (manufacturing readiness level, customer readiness level), as well as their totality. The relationship between the product lifecycle model and the matrix readiness methodology has been analyzed thoroughly. Various types of existing business intelligence, strategic and project management matrices considered. In addition, the importance of digitalization and its applicability to the methodology of matrix readiness have been outlined. The principle of flexibility in the enterprise structure has been considered.